DEVELOPMENT OF TEACHING MATERIALS FOR INTERIOR DESIGN ASSISTED WITH MULTIMEDIA APPLICATION SKETCH UP IN EDUCATION OF BUILDING ENGINEERING, FACULTY OF ENGINEERING, STATE UNIVERSITY OF JAKARTA - Virgitta, Kresna (Jurnal Pensil : Pendidikan Teknik Sipil, 2019)
This research occurred by the rise of technology and science in field of education in Indonesia. That thing requires a development and improvement of teaching material should be implemented gradually and periodically. This research aims to produce a teaching material base on electronic module assisted with multimedia application Sketch Up that help teachers and lecturer in teaching, as well can be used to gain student’s interests and expertise in the filed of Interior Design. This research use Research and Development (R&D) method which refers to Four-D model. This research was conducted through four stage of research model such as, Define, Design, Develop, and Disseminate. This research use questionnaire as instrument for collecting product eligibility data through validation from materials experts and media experts. The data analysis use the average value formula. The result of developing this teaching materials are made in 8 (eight) chapter that integrated with Sketch Up Application in some cases. Base on result of validation by material experts, got a percentage of eligibility of 85.833% which in very eligible criteria, and result of validation by media experts, got a percentage of eligibility of 75.294% wich in elighible criteria. So the teaching materials can be use as a learning resources for Interior Design courses.